KONSEKUENSI HUKUM ATAS KEHILANGAN ASET PERUSAHAAN BERFASILITAS PEMBEBASAN BEA MASUK - Gunawan Widjaja; Enna Budiman (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Cases of theft of company assets by unscrupulous employees are a criminal offense. Theft of company assets with entry permit facilities causes losses for the company, not only loss of assets, but also other legal consequences in the form of administrative sanctions from the government for the loss of goods with entry permit facilities. This research aims to understand the legal consequences for companies that are victims of criminal acts committed by unscrupulous employees considering that the goods stolen are imported goods with import duties exemption facilities which are the company's responsibility to the government authority that provides these facilities (for example: the Investment Coordinating Board and Directorate General of Customs and Excise). Next, examine whether administrative sanctions for the loss of company assets with import duty facilities fulfill the principles of justice for companies that are victims of theft by unscrupulous employees. This research is a Normative Juridical research with a legal approach and the concept of examining laws, research results and books to find legal theories, principles and views in the process of obtaining answers which are the main subject of this research.